The Appearance and Role of Rerum Natura in Three Digest Texts - Erdődy, János (Pázmány Law Review, 2025)
This paper explores the role of rerum natura in three pivotal texts from the Digest, demonstrating its function as an interpretative and normative principle in Roman legal thought. By analysing cases involving usufruct, property conflicts over the newborn child of a female slave, and immissiones, the study highlights how Roman jurists integrated objective reality into their legal reasoning. The investigation reveals that rerum natura provided a conceptual bridge between objective reality and positive law, aiding in the resolution of legal disputes. Through exegetical analysis, the paper enhances our understanding of how natura, natural law thinking and positive law eventually intersected in classical jurisprudence, offering valuable insights into the foundational principles of Roman legal tradition.